(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This community service activity is parts of economic empowerment and improves entrepreneurial spirit efforts to elementary up to high school students in ‘Aisyiyah organization in Pekanbaru. The objective of this activity is all students who lives in ‘Aisyiyah Girls Orphanage in Riau during spare time to vegetable farming by using verticulture method to fulfill their needs and economic empowerment. This activity was held on Sunday,September 19th 2021 at ‘Aisyiyah Girls Orphanage’s function hall for socializing cultivation by using verticulture method and improving entrepreneurial spirit. Furthermore, practicing the cultivation skill was held in the orphanage yard. The students were enthusiastic by the activity which shows by their enthusiasm during the activity. The community service is hopefully could improve students’ motivation to improve economy despite of the lack of yard and grow the entrepreneurial spirit.